Investigation into the Reliability and Encryption Performance of Wireless Signal Transmission by Network Coding Combined with Blockchain in Natural Disaster Scenarios. (11th May 2022) - Li, Ju; Shang, Fengjun
Abstract : To enhance the reliability and encryption of unmanned aerial vehicle (UAV) wireless signals in natural disaster scenarios, firstly, the present work analyzes the current wireless signal transmission mode of UAV. In addition, it discusses the efficient network coding of wireless signal transmission model and blockchain with strong encryption ability. Secondly, the signal transmission model of network coding is explored. Finally, the network coding wireless signal transmission model is combined with the blockchain wireless signal transmission model to realize efficient and encrypted data transmission. The research results show that the network coding wireless signal transmission model combined with blockchain technology realizes the maximum difference of network coding wireless signal transmission rate of 1.5 Mb/s. The model also encrypts the data in the simulation scenario of natural disasters through blockchain technology. After encryption, the data protection effect of the transmission model is significantly improved and meets the requirements of standard data transmission. Meanwhile, the wireless signal transmission model can reduce the resource occupation rate in the process of data transmission and improve the success rate and universality of data transmission in natural disaster scenarios. The probability of data being successfully protected in disaster is more than 90%. The results provide technical support for the stable transmission of wireless signals in natural disaster scenarios and provide a reference for improving the reliability and encryption of wireless signal transmission.